Developing a Holistic Approach for Constructing Rural Living Circles in the Loess Plateau—Taking Yongning Village as an Example - Mengying Wang; Mingzhi Zhang; Yingtao Qi; Dingqing Zhang; Chenguang Wang; Wenying Yao; Dian Zhou (Buildings, 2024)
Insufficient public service facilities in rural areas, which leads to failures in meeting the needs of villagers, has become a significant barrier to the high-quality development of rural regions. This issue is particularly acute in the Loess Plateau area, where the complex topography leads to scattered and independent village layouts, making it challenging to allocate service facilities based simply on distance and population. Aiming to arrange public service facilities efficiently and intensively from a “bottom-up” approach, this study, from the perspective of living circles, attempts to summarize the current usage and needs of villagers at the “village–town–county” levels, as well as to seek strategies for facility allocation in villages. This provides a scientific basis for optimizing the configuration of service facilities in the Loess Plateau area. Through field surveys based on questionnaires and interviews with over 60 households and more than 100 villagers, this study authentically reproduces a picture of their daily lives and summarizes their needs for well-configured services and facilities. The findings of this study include the following: (1) The village domain serves as a space of daily production and living for villagers, necessitating facilities for everyday purchases, activities, and elderly care; the town domain supplements the daily production and living needs of villagers, with a higher demand for production materials; the county domain, integrating urban and rural spaces, provides higher-level medical, educational, and other service facilities. (2) Within the village domain, villagers’ demands for facilities lean towards miniaturization and integration. With the increasingly aging population, the demand for elderly care and health facilities is becoming more urgent. Facilities such as activity rooms, fitness equipment, and stores with a wide range of products at reasonable prices can effectively improve levels of convenience and happiness in villagers’ lives. This study summarizes, from a “bottom-up” approach, the villagers’ facility layout needs within the rural living circle, providing a scientific basis for establishing a human-centered rural living circle and enhancing the quality of rural living environments.